A model for testing the hypothesis that X is necessary but not sufficient for Y - Ilagan, Michael John S.
Abstract (Some research hypothesis relate a pair of variables in terms of logical necessity and sufficiency. In psychology, one such hypothesis is that intelligence is necessary but not sufficient for creativity, unintelligent individuals are uncreative, but intelligent individuals may or may not be creative. Such a relationship is nonlinear. However, conventional statistical methods available to social scientists are inherently linear, so argument toward such a form of relationship have tested on shaky ground. Proposed is a probability model where the predictor X is necessary but not sufficient for the response Y. This model is used to realize some intelligence vs. creativity data. The necessary-but-not-sufficient relationship was supported for two out of the three creativity variables used).
May 2017.
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Probabilities; Distribution (Probability theory)